Design of a wireless device for monitoring human critical condition at industrial industrial workplace - Hamid, Nur Zamira; Asnawi, Ani Liza; W.Morshidi, W. Hafiy; Ruslan, Ahmad Alhadi; Jundi, Nurul Atiqah; Mohd Ramli, Huda Adibah (IEEE, 2018)
As many cases of accidents have been reported especially in industrial area, it is very crucial to take an initiative to reduce the accidents rate. The aim of this project is to design and develop an IoT device that is capable of monitoring human critical condition at industrial workplace. This device can help in giving forewarning to the person in charge about the surrounding of the worker if it is harmful for him/her. Besides, if the accident is already occurred, this device can help in reducing the time between the moment the accident happen and the moment the emergency care is taken to avoid any possible serious problem. This device uses several types of sensors to detect the surrounding temperature and air quality level, and movement of the user. The methods for developing this device is divided into three parts which is coding the microcontroller to accept the raw data, then connect the previous configuration with Wi-Fi module, and finally connect the whole previous data with web server, Thingspeak. The results succefully showed the reading from all sensors which include surrounding temperature, air quality level, normal and rotational acceleration, and emergency push button data. It is expected that this device can be one of the initiatives to help reducing the accidents rate in workplace especially in industrial area.